Antimicrobial peptides as drugs with double response against Mycobacterium tuberculosis coinfections in lung cancer - Polinário, Giulia; Primo, Laura Maria Duran Gleriani; Rosa, Maiara Alane Baraldi Cerquetani; Dett, Freddy Humberto Marin; Barbugli, Paula Aboud; Roque-Borda, Cesar Augusto; Pavan, Fernando Rogério (Frontiers in Microbiology, 2023)
Tuberculosis and lung cancer are, in many cases, correlated diseases that can be confused because they have similar symptoms. Many meta-analyses have proven that there is a greater chance of developing lung cancer in patients who have active pulmonary tuberculosis. It is, therefore, important to monitor the patient for a long time after recovery and search for combined therapies that can treat both diseases, as well as face the great problem of drug resistance. Peptides are molecules derived from the breakdown of proteins, and the membranolytic class is already being studied. It has been proposed that these molecules destabilize cellular homeostasis, performing a dual antimicrobial and anticancer function and offering several possibilities of adaptation for adequate delivery and action. In this review, we focus on two important reason for the use of multifunctional peptides or peptides, namely the double activity and no harmful effects on humans. We review some of the main antimicrobial and anti-inflammatory bioactive peptides and highlight four that have anti-tuberculosis and anti-cancer activity, which may contribute to obtaining drugs with this dual functionality.